Dietary intake and food preferences of institutionalized and non-institutionalized elderly - Macatangay, Lourdes A. 1951-; Florencio, Cecilia A. (1983)
This study aimed to determine the adequacy of the food and nutrient intakes and food and method of cooking preferences of institutionalized and non-institutionalized elderly. Data were gathered through the use of food weighing, interviews, and by actual observations by six nutritionist/dietitians, previously trained for the study. Thirty non-institutionalized and an equal number of institutionalized elderly from Metro Manila constituted the sample. The usual breakfast of the institutionalized subjects was made up of beverage and bread while their non-institutionalized counterparts had beverage and cereals, and meat, fish, or eggs, occasionally. The usual lunch and supper meals of the institutionalized elderly were composed of cereals and vegetables while the non-institutionalized subjects had cereals, vegetables and meat or fish. Both groups of elderly liked a particular food because of familiarity, taste, and/or health reasons. Foods were disliked for their taste, color, odor, and/or texture. Majority of the subjects from both groups preferred their foods cooked with liquid. The mean food intakes of the institutionalized and non-institutionalized elderly were 518 grams (E.P.) and 608 grams (E.P.), respectively. Only the RDA for cereal and its products and sugar and its products was met by the former; the latter, on the other hand, met the RDA only for sugar and its products and fish, meat and poultry. The overall rating of the average diet of institutionalized elderly was "poor" while that of the non-institutionalized was "fair". Mean energy and protein intakes on the former met 79 percent and 64 percent of the RDA, respectively compared to 82 percent and 77 percent, for the latter. Both groups failed to meet 100 percent of the RDA for all the nine nutrients. Both groups had "very poor" intakes of calcium and vitamin A. Institutionalized subjects had no "good" rating in any nutrient and intake in seven of the nine nutrients was rated either "poor" or "very poor". The non-institutionalized subjects intake was "good" in two nutrients, "fair" in four, "poor" in one, and "very poor" in two.
Vita.
Thesis (M.S. Food and Nutrition)--University of the Philippines, Diliman.
Keywords: Aged -- Philippines -- Manila Metropolitan Area -- Nutrition; Food preferences -- Philippines -- Manila Metropolitan Area